2018
DOI: 10.15347/wjs/2018.007
|View full text |Cite
|
Sign up to set email alerts
|

Lead: properties, history, and applications

Abstract: Lead is a chemical element with the atomic number 82 and the symbol Pb (from the Latin plumbum). It is a heavy metal that is denser than most common materials. Lead is soft and malleable, and has a relatively low melting point. When freshly cut, lead is silvery with a hint of blue; it tarnishes to a dull gray color when exposed to air. Lead has the highest atomic number of any stable element and concludes three major decay chains of heavier elements. Lead is a relatively unreactive post-transition metal. Its w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 96 publications
0
16
0
1
Order By: Relevance
“…(Beyersmann & Hartwig, 2008). In some cases, it inhibits the absorption of important trace minerals necessary for neuronal survival and its involvement in direct formation of ROS while interrupting enzyme activity (Boldyrev, 2018;Patrick, 2006). All these evidences compromise the neuronal architecture that triggers hippocampal damages which gradually lead to loss of neuronal functions, decrease in synaptic activities and spatial F I G U R E 7 Graphical abstract illustrating the probable pathways through which melatonin supplementation targeted lead-induced neuro-cognitive shutdown, anxiety and depressive-like symptoms learning and memory impairments (cognitive deficits) as a result to neurodegeneration (Farkas et al, 2007;White et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Beyersmann & Hartwig, 2008). In some cases, it inhibits the absorption of important trace minerals necessary for neuronal survival and its involvement in direct formation of ROS while interrupting enzyme activity (Boldyrev, 2018;Patrick, 2006). All these evidences compromise the neuronal architecture that triggers hippocampal damages which gradually lead to loss of neuronal functions, decrease in synaptic activities and spatial F I G U R E 7 Graphical abstract illustrating the probable pathways through which melatonin supplementation targeted lead-induced neuro-cognitive shutdown, anxiety and depressive-like symptoms learning and memory impairments (cognitive deficits) as a result to neurodegeneration (Farkas et al, 2007;White et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This result correlates with reported studies showing maximal level of lead accumulation occurring significantly in the hippocampal region of the brain causing structural damage to the brain cell components through elevated oxidative stress and inhibition of DNA repairs (Beyersmann & Hartwig, 2008). In some cases, it inhibits the absorption of important trace minerals necessary for neuronal survival and its involvement in direct formation of ROS while interrupting enzyme activity (Boldyrev, 2018; Patrick, 2006). All these evidences compromise the neuronal architecture that triggers hippocampal damages which gradually lead to loss of neuronal functions, decrease in synaptic activities and spatial learning and memory impairments (cognitive deficits) as a result to neurodegeneration (Farkas et al., 2007; White et al., 2007).…”
Section: Discussionmentioning
confidence: 99%
“…10–12 Lead is abundantly found in nature possessing unique features, such as softness, malleability, ductility, low melting point, and resistance to corrosion, which resulted in its extensive use in different industries. 13–15 However, exposure to lead is known to cause several health problems such as coma, cancer, renal failure, and could also damage the central nervous system leading to permanent cognitive impairment. 12,16 The US Environmental Potential Agency (US EPA) indicated that the maximum allowable level of lead in drinking water is 15 μg L −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals are associated with many diseases in both humans and animals, such as immunotoxicity, changed sex hormone balance, impaired reproductive systems (low fertility), mental retardation, changed metabolism, and behavioural abnormalities (Wu et al, 2016). Lead monoxide (PbO) is a hazardous metal to humans and different ecosystems, as it is used in various industries such as paints, glass, ceramics, and batteries (Boldyrev, 2018). Humans are exposed to metals mainly by inhaling dust and fumes or by consuming contaminated water and food (Cobbina et al, 2015).…”
Section: Introductionmentioning
confidence: 99%